Difluorocyclobutylacetylenes as positive allosteric modulators of mGluR5 with reduced bioactivation potential. Issue 24 (15th December 2016) - Degnan, Andrew P.; Maxwell, Darrell; Balakrishnan, Anand; Brown, Jeffrey M.; Easton, Amy; Gulianello, Michael; Hanumegowda, Umesh; Hill-Drzewi, Melissa; Miller, Regina; Santone, Kenneth S.; Senapati, Arun; Shields, Eric E.; et al.
Graphical abstract: Abstract: Schizophrenia is a serious illness that affects millions of patients and has been associated with N -methyl-d -aspartate receptor (NMDAR) hypofunction. It has been demonstrated that activation of metabotropic glutamate receptor 5 (mGluR5) enhances NMDA receptor function, suggesting the potential utility of mGluR5 positive allosteric modulators (PAMs) in the treatment of schizophrenia. Herein we describe the optimization of an mGluR5 PAM by replacement of a phenyl with aliphatic heterocycles and carbocycles as a strategy to reduce bioactivation in a biaryl acetylene chemotype. Replacement with a difluorocyclobutane followed by further optimization culminated in the identification of compound32, a low fold shift PAM with reduced bioactivation potential. Compound32 demonstrated favorable brain uptake and robust efficacy in mouse novel object recognition (NOR) at low doses.